2003
DOI: 10.1038/sj.bjc.6601419
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous interleukin-2, interferon alpha-2b and 5-fluorouracil in metastatic renal cell carcinoma as second-line treatment after failure of previous immunotherapy: a phase II trial

Abstract: The association of interleukin-2 (IL-2), interferon alpha-2a (IFNa), 5-fluorouracil (5-FU) has been reported to induce response in metastatic renal cell carcinoma (MRCC). This study evaluated IL-2, IFNa and 5FU as second-line treatment after failure under immunotherapy. A total of 35 patients received IL-2, at 9 Â 10 6 IU m À2 , once or t.i.d, 5 days a week, every other week. Interferon alpha was administered at 6 MUI, TIW along with IL-2 every week. 5-Fluorouracil was given at 750 mg m À2 day À1 on days 1 -5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…Response rates of immunochemical therapies combining 5FU with IL2 and IFNα ranged from 1.8 to 48% (16,17). Recently, a phase II multicenter trial involving 45 patients with metastatic RCC revealed the efficacy and safety of S-1, an oral fluorinated pyrimidine that includes tegafur, a prodrug of 5FU (18).…”
Section: Introductionmentioning
confidence: 99%
“…Response rates of immunochemical therapies combining 5FU with IL2 and IFNα ranged from 1.8 to 48% (16,17). Recently, a phase II multicenter trial involving 45 patients with metastatic RCC revealed the efficacy and safety of S-1, an oral fluorinated pyrimidine that includes tegafur, a prodrug of 5FU (18).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the current first line therapy for patients with metastasized RCC involves nonspecific immunotherapy with interleukin-2 and/or IFN-a cytokines with or without 5-fluorouracil treatment albeit with only 5% to 10% durable responses (4,5). Immune escape mechanisms may be responsible for the limited success of immunotherapies in patients with RCC (6,7).…”
mentioning
confidence: 99%
“…Trials in which patients were retreated with cytokines following initial cytokine failure, despite initial promising data from small phase II trials [10], have demonstrated that therapy with a different cytokine or a different cytokine schedule is not active in this patient population [11, 17]. The largest body of evidence on second-line activity of cytokines comes from the CRECY trial.…”
Section: Available Data Regarding Potential Second-line Therapies In mentioning
confidence: 99%
“…Experience of second-line therapy was limited to experimental studies that mostly failed to show any benefit [9,10,11,12,13,14,15,16,17], and not an option for clinical practice, with the only available therapeutic agents, the cytokines IFN and IL-2, having activity in selected patients with untreated mRCC and no activity in patients who had received any prior treatment for their disease [9,10,11, 17]. …”
Section: Introductionmentioning
confidence: 99%